Development and Consolidation of Budgetary Forms in Vertically Integrated Structures Based on the Application of the Mobley Matrix - V.A. (Економіка, управління та адміністрування)
The article is devoted to the search for directions of consolidation of budgetary forms in vertically integrated structures. Existing methods of consolidation often differ depending on the specific activities of business entities, their financial relationships, organizational structure and other factors. The existence of such controversial issues leads to the development and implementation of the system of budgets adapted to the specifics of vertically integrated structures. The purpose of writing this article is to study the content of existing in practice of financial planning of budget forms and identification of ways to improve them with the possibility of their adaptation for vertically integrated structures. A set of interrelated budgets in a vertically integrated structure, the technology of their preparation and consolidation is called the budgetary system of the enterprise. Taking into account the complex organizational structure of such enterprises, in the process of implementing a budgeting system, it is important to identify the number of levels of budgeting (usually not more than 4). It is proved that more than four levels of budgeting system leads to complication of control over the execution of drawn budgets and impairs communication between the levels. For vertically integrated structures, the option of a consolidated (general) budget that combines a single form of cash flow budget, income and expenditure budget, balance sheet is chosen. Three options of such consolidation are most common in the economic literature: 1) formation of a single consolidated budget of a vertically integrated structure in the form of the Mobley matrix; 2) compilation of a consolidated budget of a vertically integrated structure using the Jacobs matrix; 3) a consolidated analytical balance sheet. The order of formation of the consolidated budget of vertically-integrated structure with the application of the Mobley matrix (provides the relationship and mutual consistency of the three primary forms – the budget of funds, profit and loss budget, balance sheet), which makes it possible to form information support for the centres of financial responsibility, a systematic view of the financial processes at the enterprise and simplifies the process of analysis of consolidated budget information. Prospects for further research should be linked to the study and organization of control over the execution of budget indicators and management decisions.